Investigating Intercultural Communicative Competence of Thai EFL Undergraduates: Implications for Pedagogies - Kosashunhanan, Krishna (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research investigated the intercultural communicative competence (ICC) of Thai EFL undergraduates at a private university in Bangkok, Thailand and explored the challenges and barriers that obstructed students’ ICC development. This research was a mixed-methods approach, data were collected through self-report questionnaires based on Byram’s (1997) ICC model, conversation-based quizzes, and focus group interviews. The findings reveal that the students exhibit positive attitudes and cultural sensitivity, they face challenged in applying intercultural knowledge and skills in real-world contexts. Key barriers include limited exposure to diverse cultural experiences, a curriculum that emphasized linguistic proficiency over intercultural skills, and a lack of confidence in using intercultural communication strategies. To address these issues, this study proposed pedagogical strategies that integrated cultural elements into language instruction, focusing on experiential learning, role-playing, and virtual intercultural exchanges. The study highlighted the importance of fostering both linguistic and intercultural competence to better prepare students for global communication. Limitations and suggestions for future research are also discussed.